STEPHEN HAWKING:SAMPOORNA JEEVACHARITHRAM - GEORGE VARGHESE (KOTTAYAM DC BOOKS, 2019)
Biography of Stephen Hawking, the notable theoretical physicist, cosmologist and author penned by George Varghese.This book contains many photographs recording his life and contributions.
Keywords: STEPHEN HAWKING - BIOGRAPHY